Infantile tremor syndrome: Case report (Indian Journal of Case Reports, 2024)
Infantile tremor syndrome (ITS) is a very rare disease with an incidence of <0.2% in India. Affecting children are around 1 year of age and characterized by developmental delay, skin pigmentation, and coarse tremors. Studies since 1990 conclude that ITS is caused by nutritional deficiencies, most prominently of Vitamin B12. Since lactating mothers from a poor socioeconomic background in regions where vegetarianism is prevalent because of cultural reasons are most likely to be deficient in Vitamin B12, the syndrome is most likely to affect this segment. The case described herein is unique because it is from Mangalore in India which is a coastal town with very low levels of vegetarianism. A 14-month-old girl presented with fever, vomiting, and loose stools coupled with abnormal movements of eyes, tongue, and hands which were coarse, rhythmic, continuous of low amplitude, present throughout the day, and absent during sleep. Although initial suspicions were of seizures and the patient was administered anti-epileptics, there was no improvement in the condition of the patient. On suspicions of symptoms being of ITS, an MRI-brain was done which showed diffuse mild loss of white matter. Consequently, blood investigations showed macro-to-microcytic hypochromic anemia. Thereafter, the child was started on injectable B12 supplementation and propanolol at 0.5 mg/kg/day for tremors. The child responded well clinically.